Systemic sclerosis in Asians: Are there racial differences?. Issue 2 (June 2022) - Ng, Sue-Ann; Low, Andrea Hsiu Ling
Systemic sclerosis is a multisystemic autoimmune disease characterized by vasculopathy and fibrosis. Racial factors exert a significant influence on the epidemiology, clinical manifestations, antibody profile, mortality and genetic factors in systemic sclerosis. In this review, we examined Asian systemic sclerosis cohorts reported in Asia and multi-racial cohort studies to evaluate the disease characteristics and outcomes of systemic sclerosis in Asians. Asian patients have distinct genetic susceptibility to systemic sclerosis, younger age of systemic sclerosis onset, higher frequency of diffuse skin involvement, different autoantibody profiles such as higher frequency of anti-Scl70 and anti-U1-RNP antibodies, and more severe clinical phenotype. There was a suggestion of poorer survival among Asians that may be contributed by more severe disease, socioeconomic factors and differences in healthcare systems. Recognizing the influence of racial differences in systemic sclerosis disease course is important as it has implications for appropriate treatment, monitoring and prognostication.